1959
DOI: 10.1111/j.1365-2389.1959.tb02346.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Soil Crumbs

Abstract: A model of a soil crumb is proposed in which the crumb consists of domains of orientated clay and quartz particles. A clay domain is defined as a group of clay crystals which are orientated and sufficiently close together to behave in water as a single unit. In normal agricultural soils, where calcium is the dominant exchangeable cation, the clay crystals in the crumbs are all aggregated into domains by drying. Drying to the wilting point is apparently sufficient. In the model the domains and the quartz partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
13

Year Published

1966
1966
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(50 citation statements)
references
References 24 publications
1
34
0
13
Order By: Relevance
“…A matéria orgânica e as argilas, quando se combinam com os cátions apropriados, são os principais responsáveis pela formação dos agregados, atuando como agentes cimentantes (Emerson, 1959;Brady, 1979; Silva e Kato, 1997;Six et al, 2004). Contudo, também é preciso considerar que os cátions trocáveis do solo influem no processo de agregação (Arena, 1968) de maneira positiva (Série floculante) ou negativa (Série dispersante).…”
Section: Introductionunclassified
“…A matéria orgânica e as argilas, quando se combinam com os cátions apropriados, são os principais responsáveis pela formação dos agregados, atuando como agentes cimentantes (Emerson, 1959;Brady, 1979; Silva e Kato, 1997;Six et al, 2004). Contudo, também é preciso considerar que os cátions trocáveis do solo influem no processo de agregação (Arena, 1968) de maneira positiva (Série floculante) ou negativa (Série dispersante).…”
Section: Introductionunclassified
“…Unidades compostas pela associação de filossilicatos foram originalmente chamadas de domínio (domain), isto é, "um grupo de cristais de argila orientados e suficientemente próximos para comportarem-se em água como uma única unidade" (EMERSON, 1959). O tamanho destas unidades varia entre 1 a 2 micrômetros.…”
Section: Agregação Do Solounclassified
“…The SOC protection is proportional to the specific external surface area of clay particles, and to the monolayer interfaces between clay and sand particles. Emerson (1959) found that organic matter unavailable to microbial processes is confined between the clay crystals. The stabilizing power of clay is high, thus clay soils contain more SOC than sandy soils (Wild, 1988).…”
Section: Fig 11 Distribution Of Soc In Different Aggregatesmentioning
confidence: 99%
“…Residence time of relatively labile organic matter can be about 7 years in both silt and clay particles, whereas residence time for stable organics can reach 400 years in silt and 1000 years in clay (Buyanovsky et al, 1994). Residence times of SOC in macro-and microaggregates may differ because of (1) differences in physiochemical attraction between mineral and organic particles and (2) location of organic binding agents within the aggregates (Emerson, 1959). The SOC residence time Fig.…”
Section: Current Knowledgementioning
confidence: 99%
See 1 more Smart Citation